Digital mammography : 8th international workshop, IWDM 2006, Manchester, UK, June 18-21, 2006 : proceedings - International Workshop on Digital Mammography (8th : 2006 : Manchester, England); Astley, S. (Sue) (New York, NY : Springer, 2006)
42